Long-term antibacterial activity and cytocompatibility of novel low-shrinkage-stress, remineralizing composites. Issue 7 (3rd May 2021) - Bhadila, Ghalia; Menon, Deepak; Wang, Xiaohong; Vila, Taissa; Melo, Mary Ann S.; Montaner, Silvia; Arola, Dwayne D.; Weir, Michael D.; Sun, Jirun, Hockin H. K.; Xu
Abstract: A low-shrinkage-stress (LSS), antibacterial and remineralizing nanocomposite was recently developed; however, validation of its long-term antibacterial potency in modulating human salivary-derived biofilm is an unmet need. This study aimed to evaluate the antibacterial effect of the bioactive LSS composite before and after aging in acidic solution for 90 days using a multi-species biofilm model, and to evaluate its cytotoxicity. The LSS composite consisted of urethane dimethacrylate (UDMA) and triethylene glycol divinylbenzyl ether (TEG-DVBE), 3% dimethylaminohexadecyl methacrylate (DMAHDM) and 20% nanoparticles of amorphous calcium phosphate (NACP). Biofilm colony-forming units (CFU), lactic acid production, and confocal laser scanning microscopy (3D biofilm) were evaluated before and after three months of aging. Cytotoxicity was assessed against human gingival fibroblasts (HGF). The new LSS composite presented the lowest biofilm CFU, lactic acid and biofilm biomass, compared to controls ( n  = 6, p  < 0.05). Importantly, the new composite exhibited no significant difference in antibacterial performance before and after 90-day-aging, demonstrating long-term antibacterial activity ( p  > 0.1). The LSS antibacterial and remineralizing composite presented a low cell viability at original extract that has increased with further dilutions. In conclusion, this study spotlighted that the new bioactive composite not only had a low shrinkage stress, but also down-regulated the growth of oral biofilms, reduced acid production, maintained antibacterial activity after the 90-day-aging, and did not compromise the cytocompatibility.